1985
DOI: 10.1083/jcb.101.3.871
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cooperation between vascular endothelial cells and smooth muscle cells in co-culture: changes in low density lipoprotein metabolism.

Abstract: A microcarrier co-culture system for aortic endothelial cells and smooth muscle cells (SMCs) was developed as a model for metabolic interactions between cells of the vessel wall. Low density lipoprotein (LDL) metabolism in SMCs was significantly influenced by coculture with endothelium. The numbers of high affinity receptors for LDL was increased more than twofold (range, 2.1-5.6), with concomitant increases in LDL receptor-mediated endocytosis and degradation. These effects reached a plateau at an endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 39 publications
2
32
1
Order By: Relevance
“…With respect to lysosomal CE hydrolysis, we observed decreased ACEH activity in smooth muscle cells co-cultured with endo thelial cells as compared to smooth muscle cells cultured alone (table V). These results are supported, in part, by the findings of Davies et al [57] who studied the catabolism of labeled LDL in smooth muscle cells co cultured with endothelial cells grown on mi crocarrier spheres. Their results suggest that the presence of endothelial cells enhances the uptake of LDL by co-cultured smooth muscle cells but inhibits LDL degradation.…”
Section: Cells With Smooth Muscle Cellssupporting
confidence: 79%
See 1 more Smart Citation
“…With respect to lysosomal CE hydrolysis, we observed decreased ACEH activity in smooth muscle cells co-cultured with endo thelial cells as compared to smooth muscle cells cultured alone (table V). These results are supported, in part, by the findings of Davies et al [57] who studied the catabolism of labeled LDL in smooth muscle cells co cultured with endothelial cells grown on mi crocarrier spheres. Their results suggest that the presence of endothelial cells enhances the uptake of LDL by co-cultured smooth muscle cells but inhibits LDL degradation.…”
Section: Cells With Smooth Muscle Cellssupporting
confidence: 79%
“…Their results suggest that the presence of endothelial cells enhances the uptake of LDL by co-cultured smooth muscle cells but inhibits LDL degradation. Paradoxically, they also reported that endo thelial cell-derived conditioned medium (ECDM) had an inhibitory effect on LDL binding, internalization, and degradation in co-cultured smooth muscle cells [57], In our experiments, we were unable to demonstrate an effect with ECDM on cholesterol esterifi cation or CE hydrolysis (table V, VI).…”
Section: Cells With Smooth Muscle Cellscontrasting
confidence: 43%
“…21 Endothelial cells on beads (ECBs) were exposed to 30 /xM acetylsalicylic acid for 30 minutes, washed three times, and resuspended in PBS. The ECBs were placed in the thiol-containing solutions and stimulated to secrete EDRF by exposure to shear force as previously described.…”
Section: Endothelial Cell Culturementioning
confidence: 99%
“…Human low density lipoproteins (LDL; density, 1.019-1.063) and very low density lipoproteins (VLDL; density, 0.94-1.006) were isolated by heparin-manganese precipitation from recovered plasma (American Red Cross, Needham, MA) as described previously (16), followed by assessment of purity by double radial immunodiffusion. The amino groups on the LDL were acetylated by reaction with acetic anhydride following the method of Fraenkel-Conrat (17), and the changed electrophoretic mobility of the AcLDL was verified on agarose gels (18).…”
Section: Methodsmentioning
confidence: 99%